Pelatihan Penerapan Pendekatan Kontekstual dalam Pembelajaran Tematik bagi Guru MIN Korong Gadang Kota Padang - Abdul Basit (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2021)
The goal is to have meaningful learning for MIN Korong Gadang students through the application of a contextual approach in thematic learning and learning plan documents that have thematic contextual nuances by incorporating three national education agendas, namely strengthening character education, strengthening literacy, and 21st century learning. quality learning outcomes in schools. The method of this community service activity uses the lecture, demonstration, and discussion methods. The results of this training can be declared successful. This can be seen from: (1) The attendance of participants is in accordance with the target of 95% (23 out of 25 teachers) (2) the results of the training are stated to be very good according to the analysis of the performance appraisal rubric. (3) Participants are very enthusiastic about participating in the training, which can be seen from the seriousness of participating in the training, the many questions that arise in the mentoring process and the willingness of the teacher to apply a contextual approach in thematic learning as well as create curriculum documents in the form of contextual and thematic syllabus and lesson plans that are integrative.Keywords:  approach, contextual, thematic, integrative